A multidisciplinary approach to improving the care and outcomes of patients with retinoblastoma at a pediatric cancer hospital in Egypt. (4th July 2017) - Elzomor, Hossam; Taha, Hala; Nour, Radwa; Aleieldin, Adel; Zaghloul, M. Saad; Qaddoumi, Ibrahim; Alfaar, Ahmad S.
ABSTRACT: Background : Retinoblastoma poses a substantial burden in developing countries. We conducted this study to assess the effect of implementing a multidisciplinary approach and standardized protocols for treating pediatric patients with retinoblastoma at the Children's Cancer Hospital Egypt (CCHE). Materials and Methods : In January 2011, the CCHE implemented standardized protocols for the diagnosis, treatment, and reporting of retinoblastoma cases. The hospital also introduced a new retinoblastoma management algorithm and data analysis system. In this study, we compared the pathologic features, tumor invasiveness, reporting, and survival of 276 pediatric patients who underwent enucleations of 290 eyes before or after the implementation of the retinoblastoma protocols. Results : Time to enucleation (indicating time needed for decision taking) decreased significantly within the neoadjuvant chemotherapy group for intraocular disease after January 2011 (68.7 ± 48 weeks vs. 47.3 ± 28.3 weeks; p < 0.05). Mean optic nerve stump length increased from 5.6 mm in the earlier period to 7.2 mm in the later period ( p = 0.004). The overall quality of pathology reporting also improved during the later period. The probability of 3-year survival was significantly higher for patients during the later period (94.2% vs. 79.2%; p = 0.018). Conclusions : The implementation of standardized protocols and a multidisciplinary approach improved reporting; discrepancies in disease classification and the amount of missing data were reduced; and quality measures and prognostic capabilities of the team were substantially improved. Such established data-driven practice supports faster decision making to enucleate diseased eyes and save patients' lives through providing measurable indicators.